Beginning again: Approaches to education for rehabilitation in Caribbean prisons - Niles, Bradley; Bernard, Ayodeji (Office of the UNESCO Representative in the Caribbean, 2000)
This monograph reviews education offerings in the prison systems of seven Caribbean countries. It specifically describes literacy and skills training programmes; initiatives for the development of positive values and attitudes towards the self, others and the community; and health education drives within Caribbean prisons. It also examines differences in the policies of the various government with respect to these programmes. The main sources for the information presented were the country reports produced as part of the Education for All (EFA) 2000 assessment process, research conducted on prison education, and the report of the UNESCO Workshop on “ Fostering a Culture of Peace through Education, Rehabilitation and Empowerment.” It is concluded that Caribbean countries are moving towards providing education for all, including the region’s prisoners. However, it is necessary to place much more emphasis on the various programmes in the prison systems. The major constraint seems to be the fact that the Caribbean governments, due to their ever-increasing debt, burden, burden and economic woes, are not able to provide the necessary resources to do this adequately. The main recommendation is that Caribbean states pool their resources, technology, knowledge, and expertise in order to combat the numerous obstacles to the expansion and advancement of education in prisons.
Keywords: Training programmes